2020
DOI: 10.1017/s0144686x20001063
|View full text |Cite
|
Sign up to set email alerts
|

A latent class analysis of health lifestyles and health outcomes among Chinese older adults

Abstract: Prior analyses have repeatedly documented the association between individual health behaviours and health outcomes. Nonetheless, few studies have taken a health lifestyle theory approach to examine how health lifestyle behaviours have shaped Chinese older adults’ health status. Using the most recent 2011–2012 data released by the Chinese Longitudinal Healthy Longevity Survey (CLHLS), latent class analysis was applied to identify predominant health lifestyles among Chinese older adults aged 65–105. Four distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…The majority of respondents had challenges related to sleep, alcohol, or smoking. In general, the health lifestyle profile of older Chinese adults appeared less promising [ 51 ]. Another study in Spain used LCA and identified three distinct multimorbidity patterns among Spanish adults aged 50 and older based on the presence or absence of 11 chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of respondents had challenges related to sleep, alcohol, or smoking. In general, the health lifestyle profile of older Chinese adults appeared less promising [ 51 ]. Another study in Spain used LCA and identified three distinct multimorbidity patterns among Spanish adults aged 50 and older based on the presence or absence of 11 chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among elderly Chinese, however, those who are the most socioeconomically advantaged are most likely to have the healthiest lifestyles (Zhang 2021). This outcome suggests that the higher SEShealthiest lifestyle link exists in China but is most fully evident later in life.…”
Section: Class Circumstancesmentioning
confidence: 98%
“…This seems to be the case given that studies in the United States, Western Europe, and China find that higher SES adults are more fully represented in the healthiest lifestyles, especially in middle and older ages, compared to lower strata individuals (Cockerham, Wolfe, and Bauldry 2020; de Vries et al 2008; Kroesen 2019; van den Broek 2021; Zhang 2021). Lawrence et al (2020:14) suggest that despite experimentation when younger, high SES groups “come to reject risky health lifestyles as they complete advanced education, establish long-term relationships, and enter into occupational careers.” In sum, it can be said that individual health lifestyles often include a mixture of health-promoting and health-harming behaviors that are nonetheless aligned along social gradients throughout most of the life course, with the healthiest practices usually associated with higher SES and the least healthy with lower SES.…”
Section: Updated/expanded Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents’ health lifestyles are associated with health outcomes in adolescence and young adulthood (Burdette et al 2017). Similarly, adolescent and young adult health lifestyles predict young adult health outcomes (Lawrence et al 2017), and adults’ health lifestyles are associated with health and mortality (Saint Onge and Krueger 2017; Zhang 2021). There are many complexities to consider given that relationships can vary according to the different behaviors enacted in a lifestyle and that those same behaviors have different health effects.…”
Section: Introductionmentioning
confidence: 99%